Design and Optimization of Structural Parameters of Hydraulic Retarder Blades - Md Shimul Hossain; Wang Jiaxin; Md Ruqul Merda (Peneliti Teknologi Teknik Indonesia, 2026)
Hydraulic retarders are auxiliary braking devices in heavy-duty vehicles where rotor blade structural integrity directly affects system reliability and safety. Under operational conditions, blades experience combined centrifugal and fluid pressure loading, making geometric optimization essential to prevent stress concentration and deformation failure. This study employs finite element analysis to conduct a systematic parametric investigation of rotor blade design. Four key parameters—blade number (32-36), thickness (3-5 mm), wedge angle (35°-50°), and material (structural steel, AISI 4140, aluminum bronze, CFRP)—were evaluated under identical operating conditions (2000 rpm rotational velocity, 0.5 MPa uniform pressure). Equivalent stress, deformation, strain, and safety factor were used as comparative metrics. Results demonstrate that geometric optimization significantly outperforms material addition in improving structural performance. The optimized configuration achieves substantially enhanced safety margins while maintaining deformation within elastic limits. Material comparison identifies AISI 4140 as offering the optimal balance of strength and stiffness. These findings provide quantifiable design guidance for hydraulic retarder development and establish a systematic optimization framework applicable to rotating machinery components.